The Marmara earthquake: Epidemiological analysis of the victims with nephrological problems - (:unkn) unknown (ELSEVIER SCIENCE INC, 2001)
Background. Crush syndrome resulting from earthquakes is a major cause of morbidity and mortality, as seen during the catastrophic Marmara earthquake that struck Northwestern Turkey in August 1999. This report analyzes the epidemiological characteristics of the crush syndrome victims of this disaster. Methods. In order to analyze the nephrological problems caused by this earthquake, questionnaires were prepared within the first week of the disaster and sent to 35 reference hospitals that treated the victims. Data obtained by these questionnaires are the subject of this report. Results. Of the 5302 hospitalized patients in reference hospitals, 639 (12.0%) suffered from nephrological problems, and 477 (9.0%) needed dialysis support. Considering the patients with renal problems, there was not any significant difference in gender; however, the incidence of children younger than 10 years and the older population (older than 60 years of age) was significantly lower as compared with the resident population of the affected area (P < 0.001). Nonsurvivors were older (34.5 +/- 16.1 years) than survivors (31.2 +/- 14.4 years, P = 0.048), while no deaths were recorded under the age of 10. Most patients (70.1%) were admitted within the first three days after the earthquake, and the mortality rate among these victims was higher (17.7%) as compared with victims admitted thereafter (10.0%, P = 0.016). The average time period under the rubble was 11.7 +/- 14.3 hours, which was not significantly different between survivors and nonsurvivors, while the victims who required dialysis support spent shorter durations under the rubble, as compared with the ones who were not dialyzed at all (10.3 +/- 9.5 vs. 15.9 +/- 23.1 hours, P < 0.001). Conclusion. Victims of catastrophic earthquakes are characterized by a high incidence of renal problems and the need for dialysis support. The incidence of nephrological problems is lower in children, while the period of time under the rubble is not a prognostic indicator of survival.
Keywords: ISN Disaster Relief Task Force; crush syndrome; natural disaster; rhabdomyolysis; acute renal failure; Turkey; rescue operations; HANSHIN-AWAJI-EARTHQUAKE; ACUTE-RENAL-FAILURE; LOMA-PRIETA EARTHQUAKE; CRUSH-SYNDROME; INJURIES; DISASTERS; RHABDOMYOLYSIS; DIALYSIS